The Real-World Efficacy of Cladribine Tablets and Treatment Persistence in People with Highly Active Relapsing Multiple Sclerosis in Finland – A Follow-up Study After Four Years of Observation - Rauma, Ilkka; Viitala, Matias; Soilu-Hänninen, Merja; Atula, Sari; Laakso, Sini; Kuusisto, Hanna; Niiranen, Marja; Ryytty, Mervi; Manni, Visa (Elsevier BV, 2026)
Background
Cladribine tablets for highly active relapsing multiple sclerosis (MS) have been available in Finland since 2018. The efficacy and safety of cladribine tablets in Finland were reported in 2022. This follow-up study investigated the efficacy, treatment persistence and safety of cladribine tablets after four years.
Methods
Data of subjects who had initiated cladribine tablets for MS in 2018–2020 were acquired from the Finnish MS registry, covering 17 of 21 well-being services counties (ca. 90 % of Finnish patients) in Finland.
Results
Altogether 191 subjects were identified. The mean observation time was 4.6 years (standard deviation [SD] 0.75), and the mean efficacy follow-up was 3.6 years (SD 0.75). Mean annualized relapse rate was 1.0 (SD 0.88) at baseline, and 0.2 (SD 0.33) during the efficacy follow-up. At four years, the estimated probability of first relapse was 0.39 (95 % confidence interval [CI] 0.31–0.45) and the estimated probability of three-month confirmed disability progression (3mCDP) was 0.18 (95 % CI 0.11–0.24). Cladribine tablets were switched to other therapies in 63 subjects (33.0 %), mostly due to inefficacy (52/63, 82.5 %). No differences in the probability of first relapse, 3mCDP or switching therapy were observed between treatment-naive (60/191, 31.4 %) and treatment-experienced (131/191, 68.6 %) subjects. No grade IV lymphopenia and only one case of herpes zoster reactivation (0.5 %) were reported.
Conclusions
Efficacy was comparable across subgroups. Estimated treatment persistence at four years was 70 %. Treatment safety was comparable to previous literature. Adverse events were more frequent in subjects aged 50 years or older at treatment initiation.